Diverse perspectives on inclusive school communities - Tsokova, Diana; Tarr, Jane. (Abingdon, Oxon : Routledge, 2012)
'What is an inclusive school community? How do stakeholders perceive their roles and responsibilities towards inclusive school communities? How can school communities become more inclusive through engagement with individual perspectives? Diverse Perspectives on Inclusive School Communities captures and presents the voices of a wide range of stakeholders including young people and their parents, teachers, support staff, educational psychologists, social workers and health practitioners, in producing a collection of varied perspectives on inclusive education. In this fascinating book ,Tsokova and Tarr uniquely assemble a compilation of accounts collected through in-depth interviews with over twenty-five participants, met throughout the course of their professional lives. The authors focus on how we can ensure all children with additional support requirements, whether these are physical, sensory, cognitive, social or emotional challenges, receive the best education and social provision with their peers in inclusive school communities. Key learning points in this book emphasise: - links between early life and educational experiences; - constructions of inclusion; - an understanding of roles and responsibilities; - the power of agency in relation to inclusive school communities. The text contributes to current debates surrounding educational policy initiatives, highlighting similarities and differences across people and professions, and illuminating a way forward for a broader consensus on the concept of inclusion and ways it can be achieved. Including both UK and international accounts from individuals at different stages of inclusive education development, this text will be valuable to anyone affiliated with inclusive schooling in a personal or professional capacity'--
Includes bibliographical references (p [117]-123) and index.
Keywords: Inclusive education; Educational equalization; Children with disabilities -- Education